STANDARDISATION OF POLYHERBAL DRUGS-CERVILON AND LUMBATON CAPSULES - Rameshwari, *K.Sudha; K, Mareeshwari; R, Singaravadivelu (International Journal of Ayurveda and Pharma Research, 2017)
Standardization of Ayurvedic formulations is an important step for the establishment of a consistent biological activity, a consistent chemical profile, or simply a quality assurance program for production and manufacturing of herbal drugs. This article reports on polyherbal drugs Cervilon and Lumbaton soft gel capsule is an effective herbal Indian Ayurvedic medicine used for the neck pain and skeleto-muscular problems such as cervical spondylosis, cervical injuries, lumbar spondylosis, lower back pain, sciatica, numbness. Samples were collected from AVN Ayurveda formulations (P) Ltd. Madurai. The drugs has been standardised on the basis of physio-chemical parameters, antifungal and antimicrobial activity. High performance thin layer chromatography [HPTLC] fingerprint profiles were carried out to analysis the identity, purity and strength of the drugs. The chemical parameter analyses such as Acid value, Saponification value, Peroxide value, Iodine value are calculated and it was observed that all the values within the limits. Preliminary phytochemical analysis of the methanol extract of soft gel capsules of Cervilon and Lumbaton revealed the presence of various bioactive components which include carbohydrate, protein, alkaloids, flavanoids, and saponins. There is no fungal count was observed in plates. Antimicrobial activity was observed in soft gel capsules. They showed significant inhibition in disease causing bacteria. Selected poly herbal capsule have passed through all the WHO parameters which were tested. So it can be concluded that use of capsule was safer and ready to use.